Case report: Diagnosis and surgical treatment of delayed traumatic diaphragmatic hernia with hepatothorax and enterothorax in a small dog - Shao, Bing; Liu, Yiding; Tai, Tiange; Liu, Zhaoyang; Han, Tianyu; Yang, Yu; Fei, Shanshan; Wang, Shu; Wang, Haibin; Chen, Tiezhu; Shi, Guangliang (Frontiers in Veterinary Science, 2024)
An 8-year-old castrated male teddy bear dog presented to our clinic with a persistent cough. The sick dog suffered from vehicular trauma six months prior to the visit and had imaging and exploratory laparotomy. Imaging and exploratory laparotomy at the time showed no significant damage. We performed contrast radiography (barium gavage) on the sick dog. Based on the results of a complete contrast radiography (barium gavage), tubular shadows in the thoracic cavity were identified as the small intestine and cecum, and delayed traumatic diaphragmatic hernia with hepatothorax and enterothorax was confirmed with radiographs. Accordingly, the sick dog underwent general anesthesia, manual ventilation and diaphragmatic herniorrhaphy by standard ventral midline abdominal approach. Postoperatively, the dog were given analgesia and antibacterial treatment, and the liver biochemical indexes were monitored to prevent endotoxin. Postoperative radiographs revealed clear contours of thoracic and abdominal organs. The dog moved, ate, and urinated normally within 10 days of the surgery. This case provides a reference for a complete barium meal imaging procedure that clearly shows the position of the organs in the thoracoabdominal cavity after the occurrence of a delayed traumatic diaphragmatic hernia. This paper provides a practical reference for the diagnosis of delayed traumatic diaphragmatic hernia with hepatothorax and enterothorax.